Governing the groundwater economy: comparative analysis of national institutions and policies in South Asia, China and Mexico - Shah, Tushaar (2005)
In many parts of the world, especially in South Asia, the size of the groundwater economy has rapidly grown during the past 5 decades, and is growing still. Elsewhere in Asia— Sri Lanka, Vietnam, Laos, Thailand — and in Maghreb countries, groundwater use in agriculture has begun to grow during the past decade and is likely to peak in the coming 10 years. Global concerns with growing groundwater use in agriculture have focused mostly on its sustainability, quality degradation and adverse impacts on environment and ecological flows. Direct regulation of groundwater draft through stringent laws, regulatory frameworks and aggressive water pricing has been strongly advocated. However, despite the consensus for need to move in these directions, many governments have dragged their feet in operationalizing direct regulation. Where governments have taken pro-active stance, as in Mexico and to lesser extent, China, the impacts are variable. Governing groundwater economies is proving intractable; and responses to intensive groundwater use vary widely across nations. This paper attempts to understand why. It also argues that particularly in Asia, direct regulation of groundwater use may remain a pipe dream for a long time to come; and for effective governance of the groundwater economy, there is need to invent a wider toolkit - including direct and indirect instruments of management - that can be adapted to peculiar contexts of the groundwater economy in different countries.